2015
DOI: 10.1001/jamaophthalmol.2014.5627
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Factors in Conjunctival UV Autofluorescence

Abstract: IMPORTANCE Conjunctival UV autofluorescence (CUVAF) photography was developed to detect and characterize preclinical sunlight-induced ocular damage. Ocular sun exposure has been related to cases of pterygia and was recently negatively correlated with myopia. Hence, CUVAF has excellent potential as an objective biomarker of sun exposure. However, much variation in CUVAF has been observed, and the relative contributions of genes and environment to this variation have not yet been identified. OBJECTIVE To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
2
24
1
1
Order By: Relevance
“…Notably, self-report methods used for measuring past outdoor/sunlight exposure are likely to be imprecise and collapsing the data to two categories (high vs low) within the analysis further increases the risk of residual confounding. Yazar and colleagues sought to overcome self-report bias by using conjunctival UV autofluorescence (CUVAF) photography as a marker of cumulative exposure to UV radiation 46. However, the time course of development of damage detected by CUVAF has not yet been well-defined.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, self-report methods used for measuring past outdoor/sunlight exposure are likely to be imprecise and collapsing the data to two categories (high vs low) within the analysis further increases the risk of residual confounding. Yazar and colleagues sought to overcome self-report bias by using conjunctival UV autofluorescence (CUVAF) photography as a marker of cumulative exposure to UV radiation 46. However, the time course of development of damage detected by CUVAF has not yet been well-defined.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic susceptibility may also promote CUVAF in addition to UV damage acquired through sun exposure. Yazar et al 38 explored the hereditability of CUVAF in twins participating in the Twins Eye Study in Tasmania (n = 146, mean 12 years, range 5-51 years), the Brisbane Adolescent Twin Study (n = 444, mean 19 years, 13-28 years) and singletons recruited in the Raine study (n = 661, mean 20 years,18-22 years). The results indicated that although UV exposure contributed most significantly to CUVAF area, genetics were also associated with CUVAF area after accounting for age and gender.…”
Section: Cuvaf and Sun Exposurementioning
confidence: 99%
“…The fluorophore responsible for CUVAF is unknown. Lipofuscin, collagen cross‐links, tryptophan, nicotinamide adenine dinucleotide (NADH), or more generally, the presence of altered cellular or mitochondrial activity, have all been suggested as potential sources . Pingueculae autofluoresce strongly on CUVAF imaging and contain elastotic material and advanced glycation end‐products (AGEs), both of which autofluoresce in the cornea and skin .…”
Section: Introductionmentioning
confidence: 99%
“…Lipofuscin, collagen cross-links, tryptophan, nicotinamide adenine dinucleotide (NADH), or more generally, the presence of altered cellular or mitochondrial activity, have all been suggested as potential sources. 11,18,19 Pingueculae autofluoresce strongly on CUVAF imaging and contain elastotic material and advanced glycation end-products (AGEs), both of which autofluoresce in the cornea and skin. 6,18,[20][21][22][23] Some AGEs form by cross-linking with proteins such as collagen or elastin and UV exposure can speed up this process.…”
Section: Introductionmentioning
confidence: 99%